Zinc-air cell employing laccase as the oxygen reduction catalyst - Ahmad, Abdul Aziz; Yusof, Faridah; Abd. Wahab, Mohd. Firdaus; Othman, Raihan (2010)
Zinc-air cell employing laccase enzyme as the oxygen reduction catalyst has been investigated. Laccase is an oxidoreductase, belongs to the copper-containing enzyme family which attracts many due to its ability to reduce molecular oxygen to water. The test cell consisted of zinc metal foil as the anode and a carbon-based air electrode as the cathode, encapsulated in a single chamber, home-made acrylic board casing. The electrolyte composed of laccase and syringaldazine in a potassium dihydrogen phosphate buffer. The performance of the cell was also evaluated using sodium citrate buffer and potassium citrate buffer. Zinc-air cell utilizing laccase biocatalyst registered an open circuit voltage of 1.2 V and was able to sustain a discharge load of 500 A.